Development and scale‐up of a commercial fed batch refolding process for an anti‐CD22 two chain immunotoxin. (2nd September 2014) - Linke, Thomas; Aspelund, Matthew T.; Thompson, Christopher; Xi, Guoling; Fulton, Andrew; Wendeler, Michaela; Pabst, Timothy M.; Wang, Xiangyang; Wang, William K.; Ram, Kripa; Hunter, Alan K.
<x xml:space="preserve">Abstract</x> We describe the development and scale‐up of a novel two chain immunotoxin refolding process. This work provides a case study comparing a clinical manufacturing process and the commercial process developed to replace it. While the clinical process produced high quality material, it suffered from low yield and high yield variability. A systematic approach to process development and understanding led to a number of improvements that were implemented in the commercial process. These include a shorter inclusion body recovery process, limiting the formation of an undesired deamidated species and the implementation of fed batch dilution refolding for increased refold titers. The use of a combination of urea, arginine and DTT for capture column cleaning restored the binding capacity of the capture step column and resulted in consistent capture step yields compared to the clinical process. Scalability is shown with data from 250 L and 950 L scale refolding processes. Compared to the clinical process it replaces, the commercial process demonstrated a greater than fivefold improvement in volumetric productivity at the 950 L refolding scale. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1380–1389, 2014